2021
DOI: 10.18280/ijht.390431
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and Exergetic Assessment of the Cooling Efficiency of Automobile Radiator Using Mono and Hybrid Nanofluids

Abstract: In this paper, for two separate half-breed Nano liquids, Ag (25nm) + refined water and Ag (50nm) + Zn (50nm)-refined water tentatively considered at the vehicle radiator, the execution of restricted convection. Four distinct cross-breed Nano liquid concentrations in the range of 2-6 vol %. The increase of half breed nanoparticles into the refined water as a base liquid was organized by percentage. Within the range of 20 l/min-60 l /min, the coolant flow rate is altered. Inside the warm trade, Crossover Nano co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In their study, Sultan et al 3 analyzed the impact of Nano fluids on the velocity and thermal interfaces in the curved areas of radiator pipes. They found that the velocity magnitude was primarily affected by Nano fluids, resulting in quick thermal interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Sultan et al 3 analyzed the impact of Nano fluids on the velocity and thermal interfaces in the curved areas of radiator pipes. They found that the velocity magnitude was primarily affected by Nano fluids, resulting in quick thermal interfaces.…”
Section: Introductionmentioning
confidence: 99%